Case report of modified Box and Blocks test with motion capture to measure prosthetic function - Hebert, Jacqueline S.; Lewicke, Justin (Journal of rehabilitation research and development, 2012)
This case study report demonstrates the use of motion analysis with a modification of the Box and Blocks test. The goal was to quantify observed improvements in compensatory movements and simultaneous control in a subject using different prostheses before and after targeted muscle reinnervation (TMR) surgery. This is a single case study with data collection using a body-powered prosthesis pre-TMR surgery and 6 mo postfitting with a TMR myoelectric prosthesis. The Box and Blocks test was modified for cyclical motion within a motion capture laboratory. With the TMR myoelectric prosthesis, the subject was able to simultaneously activate the hand and elbow. Task performance was slower, but there was improved elbow flexion and less trunk compensatory motion than with the body-powered prosthesis. There are several limitations to the case study because there is no direct comparison of myoelectric performance before and after TMR surgery; however, the current report presents a potential method to quantify quality of motion and compensatory movements of prosthetic users. With further study, this test procedure has the potential to be a useful outcome measure for future standardized assessments of upper-limb prosthetic function.